Habitat Type-Based Assemblage and Distribution Prediction of Small Mammals and Chigger Mites (Acari: Trombiculidae) in Chuncheon City, Republic of Korea - Kiyoon Kim; Jusun Hwang; Kyungmin Kim; Kwangbae Yoon; Daehyun Oh; Yungchul Park (Animals)
While urbanization leads to habitat loss for medium and large mammals, small mammals can survive in fragmented habitats. As they are known to be the primary hosts of chigger mites (Acari: Trombiculidae) that transmit scrub typhus, their habitat can be considered the primary distribution area for chigger mites. This study aims to examine the distribution of small mammals and chigger mites in four habitat types and analyzed species richness, mean intensity (MI), dominance, and infestation rate (IR). A total of six small mammal species were captured, 76.8% of which were identified as Apodemus agrarius. Species richness of small mammals was highest in forests, followed by ecotones, grasslands, and agricultural lands. Apodemus agrarius accounted for 61% of the captures in forests, 80% in ecotones, 84% in grasslands, and 50% in agricultural lands, highlighting its varying dominance across habitat types. The MI of chigger mites was higher in grasslands (215.41 ± 20.70) and ecotones (171.67 ± 30.33) and lower in forests (76.67 ± 32.11). The MI of chigger mites was higher in the fall than that in the spring, and according to the MaxEnt model, they had a narrow, dense distribution in the fall and a wide distribution in the spring. These results suggest that inducing increased species richness of small mammalian hosts by habitat management and vegetation diversification may contribute to a reduction in the MI of chigger mites.